2016
DOI: 10.1016/j.jtcvs.2015.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Early and late outcomes of repaired acute DeBakey type I aortic dissection after graft replacement

Abstract: The operative mortality of patients with acute DeBakey type I aortic dissection treated by total arch replacement was acceptable with good long-term survival after both total arch replacement and non-total arch replacement. The frequency of distal aortic events might be reduced in patients after total arch replacement compared with non-total arch replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 23 publications
(26 reference statements)
2
127
1
Order By: Relevance
“…We have excluded studies with an NOS score of less than seven due to risk of substantial bias. Our up to date search strategy resulted in six more key and balanced studies (12,(18)(19)(20)(21)(22) comparing conservative versus extensive arch replacement, resulting in comparison of 1,435 conservative hemiarch replacement and 786 extensive total arch replacement as opposed to 1,236 proximal and 646 extensive replacement in the earlier published review. The estimates provided by our review for long-term follow-up data are more robust due to inclusion of more follow-up studies and time-to-event analysis of freedom from aortic re-operation, in addition to initial published studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have excluded studies with an NOS score of less than seven due to risk of substantial bias. Our up to date search strategy resulted in six more key and balanced studies (12,(18)(19)(20)(21)(22) comparing conservative versus extensive arch replacement, resulting in comparison of 1,435 conservative hemiarch replacement and 786 extensive total arch replacement as opposed to 1,236 proximal and 646 extensive replacement in the earlier published review. The estimates provided by our review for long-term follow-up data are more robust due to inclusion of more follow-up studies and time-to-event analysis of freedom from aortic re-operation, in addition to initial published studies.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with an intimal tear localized along the greater curvature close to the supra-aortic vessels, total arch replacement was performed. Concomitant stent graft was deployed in eight studies (4,10,13,17,18,(20)(21)(22). In total arch replacement with frozen elephant trunk, the deployment of stent graft was described differently between studies.…”
Section: Surgical Techniquementioning
confidence: 99%
“…This was due to a high proportion of patients who presented with lifethreatening complications, especially end stage organ malperfusion (P=0.03). This well-known bias has already been encountered in previous studies that proposed an extensive surgical repair of acute DeBakey I aortic dissection (13). On the other hand, the risk of devicerelated death, which remained rare in this series, might have been balanced by potentially life-saving stenting of the descending aorta (14,15).…”
Section: Discussionmentioning
confidence: 61%
“…A leading hospital treating aortic pathology reported that the mortality rate following type A AAD reached approximately 10% (5). Miscellaneous factors could contribute to improved outcomes, such as management of preoperative malperfusion syndrome, safe brain protection, and improved surgical skills.…”
Section: Surgical or Medical Outcomesmentioning
confidence: 99%
“…For patients with brain malperfusion secondary to type A AAD, case reports have described the successful use of a simple bypass circuit to maintain brain blood supply, with minimal postoperative neurologic sequelae (7). As a brain protection technique, the safety of antegrade cerebral perfusion during circulatory arrest has been verified (5,8). Endovascular repair techniques are not generally used in type A AAD.…”
Section: Surgical or Medical Outcomesmentioning
confidence: 99%